2015
DOI: 10.1017/s1743921316006128
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude variability in γ Dor and δ Sct stars observed by the Kepler spacecraft

Abstract: The NASA Kepler spacecraft data revealed a large number of multimode nonradially pulsating γ Dor and δ Sct variable star candidates. The Kepler high precision long time-series photometry makes it possible to study amplitude variations of the frequencies. We summarize recent literature on amplitude and frequency variations in pulsating variables. We are searching for amplitude variability in several dozen faint γ Doradus or δ Scuti variable-star candidates observed as part of the Kepler Guest Observer program. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Investigating Kepler δ Scuti stars, 603 stars exhibited at least one pulsation mode that varied significantly in amplitude over 4 years (Bowman et al, 2016). In more general, amplitude and/or frequency variations had been found among nearly all types of non-stochastically excited pulsators (Guzik et al, 2015). The long-term follow-up of the famous δ Scuti star, 4 CVn, showed that most pulsation modes exhibited a systematic significant period and amplitude changes on a timescale of decades (Breger et al, 2017).…”
Section: Newest Results Of the Space Era 2006-2018mentioning
confidence: 99%
“…Investigating Kepler δ Scuti stars, 603 stars exhibited at least one pulsation mode that varied significantly in amplitude over 4 years (Bowman et al, 2016). In more general, amplitude and/or frequency variations had been found among nearly all types of non-stochastically excited pulsators (Guzik et al, 2015). The long-term follow-up of the famous δ Scuti star, 4 CVn, showed that most pulsation modes exhibited a systematic significant period and amplitude changes on a timescale of decades (Breger et al, 2017).…”
Section: Newest Results Of the Space Era 2006-2018mentioning
confidence: 99%